The role of the graft in establishing tolerance. - Karim, M; Steger, U; Bushell, A; Wood, K (2002)
At the present time, clinical solid organ transplantation continues to rely on the use of non-specific immunosuppressive protocols in order to prevent graft rejection. However, these regimens bring with them complications related both to the global immunosuppression that they cause, and to toxicity related to individual drugs. The pursuit of protocols that will allow graft-specific tolerance thus remains a major goal of research both in animal models and in clinical practice. There is evidence that the graft itself may play an active part in establishing and maintaining donor-specific hyporesponsiveness and ultimately tolerance; the aim of this review is to analyze this role in more detail.